ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMBELIAN ULANG: Studi Empiris Pada Konsumen Tsabita Bakery di Surakarta - Nurhayati, Khairun; , Wiyadi, Ph.D; , Soepatini, Ph.D (2016)
The purpose of this study was to analyze the influence of brand image, promotion, price, quality of product to re-purchase interest Tsabita Bakery in Surakarta. The data used are primary data obtained from 105 respondents' answers were taken with non probability sampling technique. The data required is obtained through the questionnaire method. Previous questionnaires have been tested-piloted and tested for validity and reliability were tested. Classic assumption test results show that the normal distribution of data, nothing happens multikolinearitas, did not happen heteroskedastisitas, and has been linear. Data analysis technique used is multiple linear regression analysis, the coefficient of determination (R2), the F test (precision model), t test (accuracy parameter). Results of regression analysis regression equation: brand image variables to give a significant positive effect on repurchase interest. Promotion variables significant positive effect on the interest The purchase again. Variable rates had a negative impact significantly on the interest The purchase again. and the variable quality of the products is a significant positive effect on repurchase interest.